Transgenic and genome-edited fruits: background, constraints, benefits, and commercial opportunities. (17th July 2021) - Lobato-Gómez, Maria; Hewitt, Seanna; Capell, Teresa; Christou, Paul; Dhingra, Amit; Girón-Calva, Patricia Sarai
Abstract: Breeding has been used successfully for many years in the fruit industry, giving rise to most of today's commercial fruit cultivars. More recently, new molecular breeding techniques have addressed some of the constraints of conventional breeding. However, the development and commercial introduction of such novel fruits has been slow and limited with only five genetically engineered fruits currently produced as commercial varieties—virus-resistant papaya and squash were commercialized 25 years ago, whereas insect-resistant eggplant, non-browning apple, and pink-fleshed pineapple have been approved for commercialization within the last 6 years and production continues to increase every year. Advances in molecular genetics, particularly the new wave of genome editing technologies, provide opportunities to develop new fruit cultivars more rapidly. Our review, emphasizes the socioeconomic impact of current commercial fruit cultivars developed by genetic engineering and the potential impact of genome editing on the development of improved cultivars at an accelerated rate.